PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN SIM CARD KARTUHALO TELKOMSEL REGIONAL MALUKU : (UNIT PELAYANAN GRAPARI MALUKU) - Wattimena, Roy Alan (Politeknik Negeri Ambon, 2020)
The Maluku GraPARI Service Unit is currently faced with a business competition in cellular telecommunications operator services with a number of other cellular telecommunications operators in the country. The problem of this research is how the effect of service quality on SIMCard GSM kartuHALLO customer satisfaction and the purpose of this research is to test and analyze service quality on SIMCard GSM kartuHALLO customer satisfaction.This research was conducted to achieve the research objectives that have been set, namely to identify and analyze the level of importance of each attribute dimension of service quality in creating total customer satisfaction for SIMCard GSM kartuHALO Telkomsel services. samples taken as many as 100 samples. Data collection is carried out by distributing questionnaires to kartuHALO customers. Multiple Regression Analysis is used to measure the influence of the independent variables on the dependent variable.The results of the analysis show that the F-test statistical test shows that the independent variables tangible, reliability, responsiveness, assurance and empathy simultaneously have a positive and significant effect on consumer satisfaction using the SIMCard Telkomsel HALLO card.tangible, reliability, responsiveness, assurance and empathy have a positive and significant influence on kartuHALO user satisfaction. This means that every increase in tangible, reliability, responsiveness, assurance and empathy is in line with an increase in customer satisfaction. Keywords: Service Quality, Customer Satisfaction